Classifying EEG Signals Preceding Right Hand, Left Hand, Tongue, and Right Foot Movements and Motor Imageries - Morash, Valerie (2008)
OBJECTIVE: To use the neural signals preceding movement and motor imagery to predict which of four movements/motor imageries is about to occur, and to access this utility for brain-computer interface (BCI) applications. METHODS: Eight naive subjects performed or kinesthetically imagined four movements while electroencephalogram (EEG) was recorded from 29 channels over sensorimotor areas. The task was instructed with a specific stimulus (S1) and performed at a second stimulus (S2). A classifier was trained and tested offline at differentiating the EEG signals from movement/imagery preparation (the 1.5 seconds preceding movement/imagery execution). RESULTS: Accuracy of movement/imagery preparation classification varied between subjects. The system preferentially selected event related (de)synchronization (ERD/ERS) signals for classification, and high accuracies were associated with classifications that relied heavily on the ERD/ERS to discriminate movement/imagery planning. CONCLUSIONS: The ERD/ERS preceding movement and motor imagery can be used to predict which of four movements/imageries is about to occur. Prediction accuracy depends on this signal’s accessibility. SIGNIFICANCE: The ERD/ERS is the most specific pre-movement/imagery signal to the movement/imagery about to be performed.